Tenascin-C Deficiency Is Associated With Reduced Bacterial Outgrowth During Klebsiella pneumoniae-Evoked Pneumosepsis in Mice - Meijer, Mariska T.; de Vos, Alex F.; Scicluna, Brendon P.; Roelofs, Joris J.; Abou Fayçal, Chérine; Orend, Gertraud; Uhel, Fabrice; van der Poll, Tom (Frontiers in Immunology, 2021)
Tenascin C (TNC) is an extracellular matrix glycoprotein that recently emerged as an immunomodulator. TNC-deficient (TNC−/−) mice were reported to have a reduced inflammatory response upon systemic administration of lipopolysaccharide, the toxic component of gram-negative bacteria. Here, we investigated the role of TNC during gram-negative pneumonia derived sepsis. TNC+/+ and TNC−/− mice were infected with Klebsiella pneumoniae via the airways and sacrificed 24 and 42 h thereafter for further analysis. Pulmonary TNC protein levels were elevated 42 h after infection in TNC+/+ mice and remained undetectable in TNC−/− mice. TNC−/− mice showed modestly lower bacterial loads in lungs and blood, and a somewhat reduced local—but not systemic—inflammatory response. Moreover, TNC−/− and TNC+/+ mice did not differ with regard to neutrophil recruitment, lung pathology or plasma markers of distal organ injury. These results suggest that while TNC shapes the immune response during lipopolysaccharide-induced inflammation, this role may be superseded during pneumosepsis caused by a common gram-negative pathogen.